Intellectual property and investment funds - Francesca Schmitt (European Institute for Knowledge & Value Management (EIKV), 2016)
IP needs to be considered as key factor in order to create value across industries, even though it correlates with many challenges. Nonetheless, IP as asset can be interconnected with the financial markets. Therefore, intermediaries, such as investment funds are necessary. Since Luxembourg is the leading investment fund centre in Europe and second in the world, this thesis analyses how IP can be interconnected with various investment fund structures in Luxembourg. Based on this, the most suitable structure shall be evaluated. After a short description of intangible assets and its subset IP, as well as their divergent valuation approaches, investment fund vehicles in Luxembourg are addressed. Subsequently the role of IP in Luxembourg is illustrated and finally evaluated based on a SWOT analysis. In order to draw the connection between IP and investment funds, several potential investment fund structures for Luxembourg are described and analysed towards their compatibility with IP. In order to receive a practical insight, interviews have been conducted with experts from diverse knowledge fields. The results of the interviews show that currently too many divergent key challenges exist which ultimately need to be overcome before considering investment funds as intermediary between IP and the financial market. Nonetheless, currently the opportunity of setting up SPV's with a sale and lease-back structure can be utilized in order to achieve a successful interconnection. – – Um einen branchenübergreifenden Mehrwert zu schaffen, muss IP als Schlüsselfaktor erachtet werden, wenngleich dieser Vermögenswert mit einigen Herausforderungen eihergeht. Nichtdestotrotz ist es möglich IP mit dem Finanzmarkt zu verbinden. Im Rahmen dessen, sind sogenannte Intermediäre, wie beispielsweise Investmentfonds, von Nöten. Da Luxemburg innerhalb Europas als führender Finanzplatz gilt und weltweit an zweiter Stelle steht, verfolgt diese These das Ziel, die divergierenden Optionen hinsichtlich der Verflechtung von IP mit Investmentfonds in Luxemburg zu analysieren. Davon ausgehend, soll die geeignetste Struktur evaluiert werden. Nach einer kurzen Beschreibung von immateriellen Vermögenswerten, deren Teilgruppe IP, sowie die differenzierten Bewertungsansätze, sollen die unterschiedlichen Investmentfondsvehikel für Luxemburg dargestellt werden. Anschließend identifiziert die These, inwiefern IP in Luxemburg vertreten ist. Die Ergebnisse aus dieser Untersuchung werden in einer SWOT Analyse zusammengefasst. Um die Verbindung zwischen IP und Investmentfonds herzustellen, werden verschiedene Investmentfondsstrukturen für Luxemburg hinsichtlich ihrer Kompatibilität mit IP erläutert und abschließend analysiert. Des Weiteren werden Experteninterviews durchgeführt, um einen praktischen Bezug zu ermöglichen. Die Ergebnisse der Interviews weisen eine große Anzahl an zentralen Herausforderungen auf, die zunächst bewältigt werden müssen, damit Investmentfonds die Funktion als Intermediär erfüllen kann. Aufgrund dessen kann derzeit lediglich ein SPV mit einer sale und lease-back Struktur verwendet werden um eine erfolgreiche Verbindung zwischen IP und dem Finanzmarkt zu erreichen.
Keywords: 330